The Effect of ISIS on Foreign Relations Kurdistan Region – Iraq After 2014 - Barzan Jawhar Sadeq; Muhammed Ismael Jalil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The Kurdistan Region faced numerous threats as a result of the struggle against ISIS, but the region’s diplomacy and quality of external connections paid off. Because it provided the strongest ground force against ISIS, the organization’s genocide of the Yazidis in Sinjar sparked a significant worldwide response and helped to win the international community’s support and solidarity for the Kurdistan Region. The Kurdistan Region’s paradiplomatic and foreign contacts improved as a result of these events, including an increase in diplomatic delegation visits, and visits and summit-level receptions, establishing new relations, participation in international conferences and forums relevant to regional and global security.